2019
DOI: 10.1158/0008-5472.can-19-0213
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI and Coregistered Histology Identify Tumor Habitats in Breast Cancer Mouse Models

Abstract: It is well-recognized that solid tumors are genomically, anatomically, and physiologically heterogeneous. In general, more heterogeneous tumors have poorer outcomes, likely due to the increased probability of harboring therapy-resistant cells and regions. It is hypothesized that the genomic and physiologic heterogeneity are related, because physiologically distinct regions will exert variable selection pressures leading to the outgrowth of clones with variable genomic/proteomic profiles. To investigate this, m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 54 publications
3
61
0
Order By: Relevance
“…Using model comparison to identify sub‐regions shares similarities with previous efforts to characterize intra‐tumor heterogeneity using clustering or probabilistic classification of multi‐contrast MR data. While it is beyond the scope of the present work to compare model comparison and multi‐contrast approaches to identifying sub‐regions, the inclusion of additional data beyond DWI would be expected to aid the characterization.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Using model comparison to identify sub‐regions shares similarities with previous efforts to characterize intra‐tumor heterogeneity using clustering or probabilistic classification of multi‐contrast MR data. While it is beyond the scope of the present work to compare model comparison and multi‐contrast approaches to identifying sub‐regions, the inclusion of additional data beyond DWI would be expected to aid the characterization.…”
Section: Discussionmentioning
confidence: 74%
“…Spatial correspondence between histology and imaging is also hindered by shrinkage and distortion of histological samples due to fixation and sectioning. Improved methods for comparison of histology and imaging, such as the use of tumor‐specific moulds and image registration, would provide a more comprehensive biological validation. Taken together, the in vivo and in silico results suggest that %MM is related to tumor necrosis, although actual necrotic fractions will be lower than %MM suggests.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinally monitoring tumors and responses to therapy may require more frequent magnetic resonance imaging and other imaging techniques as noninvasive tools for identifying and tracking different tumor habitats based on vascularity, hypoxia, necrosis, and so on. 66,67 Pseudo-Resistance Heterogeneity in quiescence could obscure detection of resistance to treatment through the phenomenon of pseudo-resistance, a situation where an otherwise treatment-sensitive population of cancer cells appears to be resistant. Pseudoresistance could result from temporal variation that selects for cell lineages that maintain a high fraction of cells within a quiescent state.…”
Section: How Might Consideration Of the Storage Effect Inform Cancermentioning
confidence: 99%
“…In this context, if noninvasive imaging of hypoxia can be developed it would allow longitudinal monitoring of therapy response without a biopsy. We had previously developed a multiparametric MRI (mpMRI) method to identify hypoxic habitats in breast cancers using Gaussian Mixture Models (26). Herein, we take a similar approach to identify hypoxia in sarcoma using a convolutional neural network (CNN).…”
Section: Noninvasive Measurement Of Hypoxia In Mr Imagingmentioning
confidence: 99%
“…To this end, different magnetic resonance imaging (MRI)-and positron emission tomography (PET)-imaging based analyses have been explored to identify tumor hypoxia (23,24) and predict response to HAPs in pre-clinical models (19,25). We have previously reported that multiparametric (mp) MRI can capture subtle difference in the tumor microenvironments, and is able to differentiate viable, necrotic and hypoxic tumor habitats in breast cancer models (26).…”
Section: Introductionmentioning
confidence: 99%